A case of cutaneous extranodal natural killer/T‐cell lymphoma clinically and histopathologically mimicking interface dermatitis. (2nd June 2020) - Choi, Myoung Eun; Yang, Hee Joo; Lee, Woo Jin; Won, Chong Hyun; Chang, Sung Eun; Choi, Jee Ho; Lee, Mi Woo
Abstract: Extranodal natural killer/T‐cell lymphoma (ENKTL) is a rare but aggressive cancer characterised by angiocentric and angiodestructive infiltration by NK‐cells, or cytotoxic T‐cell types. Histopathologically, ENKTL shows a multinodular or diffuse infiltration localised to vascular structures, resulting in angiodestruction and necrosis. We present a patient with an initially suspected diagnosis of benign interface dermatitis with a differential diagnosis of mycosis fungoides that was later found to be an aggressive extranodal natural killer/T‐cell lymphoma of a nasal type and with a dismal prognosis.